Reconstruction of Cultivated Land in the Northeast Margin of Qinghai–Tibetan Plateau and Anthropogenic Impacts on Palaeo-Environment During the Mid-Holocene - Wende, Zhuoma; Hou, Guangliang; Gao, Jingyi; Chen, Xiaoliang; Jin, Sunmei; Lancuo, Zhuoma (Frontiers in Earth Science, 2021)
The study of past global change is paramount to comprehending the present and future, as well as to better understand the mechanisms and influences of human-land interactions in a given region. The northeastern margin of the Qinghai-Tibetan Plateau has complex natural environments, sensitive to global change, and renowned for its long history of human occupancy. This makes it an ideal region for the study of anthropogenic impacts on the paleo-natural environment. This paper reconstructed the prehistoric temporal and spatial distribution of cultivated lands on the northeast margin of Qinghai-Tibetan Plateau, and analyzed the Dianziping pollen assemblage to disclose the anthropogenic impacts on the paleo-environment. The results demonstrated that around 4.3-4.0 cal ka BP, the rapid development of the Majiayao culture boosted the population to approximately 39,200 people, over 460km2 of the land area was converted to cropland, concomitantly, evidence of tree pollen decreased significantly. This marked the earliest identification of anthropogenic impacts on vegetation through agricultural activity in this region. At 4.0-3.6 cal ka BP, the population appeared to have diminished in conjunction with the cultivated land area. Nevertheless, forested areas continued to decrease, primarily due to adverse climatic conditions, but, anthropogenic activities played an undeniable role. Dianziping profile demonstrated the existence of natural forest in the Hehuang Valley during Qijia cultural Period. There was also evidence for the occurrence of regional fire events, suggesting large-scale burning of land cover in the area. This further illustrates anthropogenic impacts. At 3.6-2.6 cal ka BP, populations reached approximately 61,300 people, coinciding with the peak of cropland expansion. Consequently, more of the natural vegetation were converted to crops, and the superimposed influences of farming and grazing aggravated the process of deforestation and vegetation succession. Likewise, deforestation during the historical period can be explained, mostly by human driven causes with limited influence from climatic factors. The extensive exploitation of forest and expansion of cropland consequently resulted in extensive land deterioration, leaving the region with forest islands scattered in less populated, mountainous regions.